Human-Leopard Conflict: An Emerging Issue of North China Leopard Conservation in Tieqiaoshan Provincial Nature Reserve in Shanxi Province, China - Kahindo Tulizo Consolee; Chunyv Gao; Kasereka Vitekere; Chunshi Li; Hua Yan; Guangshun Jiang (Animals, 2020)
Livestock depredation by large carnivores is a conventional human–wildlife conflict, both at the local and regional level. Many species of wildlife have become endangered because of this conflict. In this study, an investigation of livestock depredation was conducted for the north China leopard in and around Tieqiaoshan Provincial Nature Reserve in Shanxi Province between 2015 and 2018. Data were obtained from League Cat Forest Department records. Additionally, standardized, structured, and semi-structured questionnaires were used to collect data with the help of reserve field staff. The results show that there was a significant difference (p = 0.015) in livestock depredation in various seasons of the year; the highest depredation was recorded in spring, followed by summer. A significant difference (p = 0.02) was observed between cattle and other livestock species, showing that more cattle were killed by the north China leopard. Most of the livestock depredation occurred during late morning and evening, likely because the leopards are crepuscular. Residents in and around the reserve suffered a high economic loss, ranging between RMB 5000 and 10,000 (USD 706.76–1413.53) per year in terms of the estimated market price of the killed livestock. The attitudes of residents towards the north China leopard vary according to the economic activities of the locals, with about 76% of the livestock keepers reporting that the leopard is “very dangerous” and 8% of the arable farmers in and around the reserve indicating that leopard is “very dangerous.” We recommend that a system with local participants would ensure more effective management of human-north China leopard conflict, as it would allow local communities to take greater responsibility.